Giant condyloma acuminatum-malignant transformation. - Papapanagiotou, Ioannis K; Migklis, Kyriaki; Ioannidou, Georgia; Xesfyngi, Dimitra; Kalles, Vasileios; Mariolis-Sapsakos, Theodoros; Terzakis, Emmanouil (Clin Case Rep, 2017)
Giant condyloma acuminata are associated with malignant transformation in up to 50% of cases, high recurrence rate, and poor prognosis. Treatment strategies have included wide local excision, abdominopelvic resection, and addition of radiotherapy and adjuvant and/or neoadjuvant systemic chemotherapy.